White eye syndrome, as a cause of blindness - Avilés-Calderón, José Gustavo (2019)
The white-eye syndrome as a cause of blindness encompass a group of eye diseases whose outcome is visual loss. The etiology of these diseases is diverse, ranging from diseases associated with an increase in intraocular pressure such as openangle glaucoma, vascular occlusive diseases of the principal retinal vessels or inflammatory diseases of the optic nerve.